Brewing happiness: Is it just about coffee or more? - Yudhi Koesworodjati; Fathiyyahrohmah, Annisa (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2023)
This study aims to provide empirical evidence of the important role of product diversity and service quality on consumer’s perceived value and its subsequent influence on consumer satisfaction. The largest local coffee shop brands in Indonesia have been selected as the focal points of this study due to their amalgamation of traditional and modern flavors and the unique experiential offerings they provide to their customers. Notably, the novelty of this study resides in its intention to bridge a significant gap in the existing literature. Prior studies have rarely explored the factors associated with customer satisfaction within the context of local coffee shop services with the mediation role of perceived value and antecedents of product variability. The study adopts a quantitative research approach, utilizing a 5-point Likert scale in a survey-based methodology. A total of 262 respondents, comprising a diverse pool of coffee lovers and enthusiasts, actively participated in this survey. To examine and assess the hypotheses posited in this study, we utilized the SPSS macro-PROCESS (Model 4). The study's findings indicate a significant positive correlation between product and service diversity and customer value. This suggests that by offering a diverse range of innovative products and services, coffee shops can enhance the perceived value for customers, ultimately leading to higher satisfaction levels. Interestingly, this study has uncovered a notable difference in the role of service quality as a primary driver of customer satisfaction, in contrast to prior findings suggesting that service quality is merely one of several factors contributing to satisfaction.